Analysis of the Barriers to Continuous Improvement Commitment in the After-sales Service of the Automotive Industry - Romero-Zárate, Ricardo (2020)
This document analyses the barriers to the continuous improvement commitment (MC) in a recognized company in the automotive industry in Ecuador. With the aim of being able to understand what the reasons that contribute to this current problem of this type of companies are, where the Staff does not openly contribute neither to meeting goals nor continually improving their processes, the research was an integrated study in two automotive technical service centers in Quito, Ecuador. The integrated unit of analysis was the total population of employees and managers in an organization. Data was collected through questionnaires and semi-structured interviews. The results were triangulated. Reliability and validity procedures were used to increase the confidence levels of the results. The research showed that there are barriers in the initiative of employees to maintain a commitment to continuous improvement and development in companies, which should be overcome to implement an efficient quality system; In addition, it found that the commitment of the employees are low, affecting the effective fulfilment of their short and long term objectives. It was also shown that these barriers affect the commitment to achieve the adequacy and convenience of their quality system, which directly affects their organizational culture to achieve improvement.